KAJIAN TEOLOGIS UNGKAPAN ”CELAKALAH AKU JIKA AKU TIDAK MEMBERITAKAN INJIL” DALAM 1 KORINTUS 9:16B - Pranoto, David Susilo (Sekolah Tinggi Teologi Arastamar Bengkulu, 2018)
Individualism increasingly affects human life. This makes people busy with their respective activities. Facing such conditions, how is the urgency of evangelism today. Therefore to answer that principle, we need to understand Paul's expression which is: